Active Individual Nanoresonators Optimized for Lasing and Spasing Operation - Szenes András László; Vass Dávid Imre; Bánhelyi Balázs; Czirjákné Csete Mária (2021)
Plasmonic nanoresonators consisting of a gold nanorod and a spherical silica core and gold shell, both coated with a gain layer, were optimized to maximize the stimulated emission in the near‐field (NF‐c‐type) and the outcoupling into the far‐field (FF‐c‐type) and to enter into the spasing operation region (NF‐c*‐type). It was shown that in the case of a moderate dye concentra-tion, the nanorod has more advantages: smaller lasing threshold and larger slope efficiency and larger achieved intensities in the near‐field in addition to FF‐c‐type systems’ smaller gain and out-flow threshold, earlier dip‐to‐peak switching in the spectrum and slightly larger far‐field outcou-pling efficiency. However, the near‐field (far‐field) bandwidth is smaller for NF‐c‐type (FF‐c‐type) core–shell nanoresonators. In the case of a larger dye concentration (NF‐c*‐type), although the slope efficiency and near‐field intensity remain larger for the nanorod, the core–shell nanoresonator is more advantageous, considering the smaller lasing, outflow, absorption and extinction cross‐section thresholds and near‐field bandwidth as well as the significantly larger internal and external quantum efficiencies. It was also shown that the strong‐coupling of time‐competing plasmonic modes accompanies the transition from lasing to spasing occurring, when the extinction cross‐section crosses zero. As a result of the most efficient enhancement in the forward direction, the most uni-form far‐field distribution was achieved. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Számítás- és információtudomány; Fizikai tudományok